2018
DOI: 10.1002/anie.201811570
|View full text |Cite
|
Sign up to set email alerts
|

A Noble‐Metal‐Free Heterogeneous Photosensitizer‐Relay Catalyst Triad That Catalyzes Water Oxidation under Visible Light

Abstract: An entirely earth‐abundant chromophore‐relay water oxidation catalyst triad system, which is robust and efficient at neutral pH, is presented. The synthesis involves the coordination of a porphyrin derivative to a bridging Fe(CN)5 group, which is then reacted with Co ions to prepare a covalently linked chromophore–Prussian blue analogue assembly. Light‐driven water oxidation studies in the presence of an electron scavenger indicate that the triad is active and it maintains a steady activity for at least three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 43 publications
4
31
0
Order By: Relevance
“…Guided by our previous findings, we kept the [Fe(CN) 5 ] fragment and active Co site unchanged and screened various organic ligands (R) featuring a pyridyl group (Figure a). A combination of up‐to‐date quantum chemical calculations showed that, in line with our previous results, the critical LUMO is on the Co−O fragment (Figure a) for the active Co oxo/oxyl species . Moreover, the inclusion of a formal positive charge on the ligand by virtue of quaternized pyridyl salts resulted in a more electrophilic LUMO.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Guided by our previous findings, we kept the [Fe(CN) 5 ] fragment and active Co site unchanged and screened various organic ligands (R) featuring a pyridyl group (Figure a). A combination of up‐to‐date quantum chemical calculations showed that, in line with our previous results, the critical LUMO is on the Co−O fragment (Figure a) for the active Co oxo/oxyl species . Moreover, the inclusion of a formal positive charge on the ligand by virtue of quaternized pyridyl salts resulted in a more electrophilic LUMO.…”
Section: Resultssupporting
confidence: 86%
“…[Fe–NH 3 ] exhibits a sharp CN peak at 2031 cm −1 , which shifts to a higher wavenumber for [Fe–JG] (ca. 2058 cm −1 ) . The blue shift is evidence for not only the coordination of JG to an iron complex but also the donor–acceptor interaction between the iron site and JG, which plays a critical role in efficient electron transfer.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In recent studies, we developed a facial route based on oblique angle deposition to synthesize plasmonic nanostructures on a large scale. Moreover, we demonstrated that as a result of the cyanide chemistry, so‐called CoFe‐Prussian blue analog (PBA) is a strong and robust water oxidation catalyst (WOC), when connected to an organic chromophore . Inspired by these studies, herein, we adopt an extendable platform for the realization of a catalyst‐plasmonic architecture to improve the performance of semiconductor photoanodes with a facial and large‐scale compatible design in PEC‐WS.…”
Section: Introductionmentioning
confidence: 99%